Notary Responsibilities in Making Authentic Deeds for Interest of Community from Progressive Law Perspective - Imam Abdi Utama; Sri Kusriyah; Widhi Handoko (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
A notary is a public official who is authorized to make an authentic deed as long as the making of a certain authentic deed is not reserved for other public officials. Making authentic deeds is required by laws and regulations in order to create certainty, order and legal protection. The notary's responsibility when viewed from Act No. 30 of 2004 as amended by Act No. 2 of 2014 concerning the Position of a Notary is very closely related to the duties and work of a notary. It is said so because in addition to making authentic deeds, notaries are also assigned and responsible for registering and ratifying letters/deeds made under the hand. Progressive legal knowledge possessed by a notary will also contribute to developing knowledge about notary law. The problems in this study include how the notary's responsibility in making authentic deeds for the benefit of the community is seen from the point of view of progressive law. This study uses a normative juridical research method with descriptive research specifications where this study aims to describe a comparison of legal problems that occur in certain areas or at certain times. This study uses secondary data sources which are divided into primary legal materials, secondary and tertiary legal materials. The research results that have been collected are then analyzed qualitatively.